Particle swarm optimization algorithm for solving airline crew scheduling problem - Ezzinbi, Omar; Sarhani, Malek; El Afia, Abdellatif; Benadada, Youssef (2014 International Conference on Logistics Operations Management, 2014)
In air transport, the cost related to crew members presents one of the most important cost supported by airline companies. The objective of the crew scheduling problem is to determine a minimum-cost set of pairings so that every flight leg is assigned a qualified crew and every pairing satisfies the set of applicable work rules. In this paper, we propose a solution for the crew scheduling problem with Particle Swarm Optimization (PSO) algorithm, this solution approach is compared with the Genetic Algorithm (GA) for both crew pairing and crew assignment problems which are the two part of crew scheduling problem.